2014
DOI: 10.5536/kjps.2014.41.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Energy Metabolism and Protein Utilization in Chicken- A Review

Abstract: Evaluation of energy in the diet is very important in animal nutrition because food intake is strongly influenced by the energy content of the diet. This means that the intake of other nutrients, such as amino acids, is affected by their ratio to energy content. Poultry can control their energy intake over a range of energy: protein ratios. Energy: protein ratio also affects the growth and body composition. Therefore we need to know what extent the relationship between energy and dietary protein influences the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition, the result of the present study showed that HI decreased in the test diet group compared with the basal diet group of BJY1 and BJY2 chickens, which could be explained by the lower nitrogen excretion. Because the surplus amino acids would stimulate an additional increase in metabolic rate and lead to increased energetic costs of catabolism and excretion (Kim, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the result of the present study showed that HI decreased in the test diet group compared with the basal diet group of BJY1 and BJY2 chickens, which could be explained by the lower nitrogen excretion. Because the surplus amino acids would stimulate an additional increase in metabolic rate and lead to increased energetic costs of catabolism and excretion (Kim, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It may be that the fat content in gained body weight was higher in slow-growing chickens than in fast-growing chickens (Zelenka et al, 2011), fat tissue contributes little to HP compared with that of muscle, and animals with high-fat rates have lower energy requirements than animals with low-fat rates (Close, 1990). Macleod et al (1988) metabolic rate and lead to increased energetic costs of catabolism and excretion (Kim, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the energy in the diet is imperative in animal nutrition because feed intake is strongly influenced by the energy content of the diet. This implies that the intake of other nutrients such as amino acids is affected by their ratio to the energy content of the feed consumed by the animal (Kim, 2014). For this reason, understanding energy metabolism in poultry is important to determine the exact energy utilization capacity and requirement of the poultry species specifically when comparing a native breed to their commercial breed counterparts.…”
Section: A Feed Energy Utilization With Emphasis On Ducksmentioning
confidence: 99%
“…Different energy evaluating systems have been used to formulate poultry diets including digestible energy, total digestible nutrients, true metabolizable energy, apparent metabolizable energy (AME), and effective energy. The ME system or AME values of raw materials are most commonly and widely used to formulate poultry diets (Barzegar et al, 2020;Kim, 2014). This is because of the exceptional digestive anatomy of poultry species where the feces and uric acid excreted by the birds are mixed in the cloaca, a single opening at the end of the digestive tract (Dunaway, 2019).…”
Section: B Apparent and True Metabolizable Energy Values Of Corn And ...mentioning
confidence: 99%